Improving ecological properties of gasolines by the catalytic hydrogenation of fraction of gasoline after reforming - Кравченко, Є.В.; Кочірко, Б.Ф.; Деркач, В.Л.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2005)
Catalytic process of hydrogenation of gasoline after reforming as one of the methods to improve ecological properties of gasolines has been considered. It was studied the composition of initial raw materials, separated fraction i.b.p. - 90ºC before and after hydrogenation and the mixture of components for a preparation of high octane component for gasolines.